The Representation of Masculinity through Peter Parker as the Main Character in Spider-Man No Way Home Movie - Hidayatun Ni’mah; Dyah Kurniawati (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2022)
This research aims at analyzing the personal characteristics of Peter Parker character in Spider-Man No Way Home movie using Masculinity theory. This research focuses on explaining and analyzing the masculinity characteristics and its type founded in Peter Parker as the main character in this movie. This research used a descriptive qualitative method. Procedure of collecting and analyzing the data in this research are preparing the data, selecting the data, watching the movie to obtain the data.While in analyzing the data, the researchers employ some steps as follows: analyzing the data, identifying the data, coding the data, describing the data and making the report. This research finds the Masculinity characteristics in the main character based on Janet Saltzman Chafetz’s theory. Based on the references used in this study, Peter Parker has all the characteristics of masculinity: physical, function of the man, sexual aggressive, emotion, intellectual, interpersonal and other personal characteristics. Based on the film and the references it shows that Peter Parker has a hegemony type of masculinity.